Screening Nature Cinema Beyond the Human - Pick, Anat; Narraway, Guinevere (Berghahn Books, 2013)
Environmentalism and ecology are areas of rapid growth in academia and society at large. Screening Nature is the first comprehensive work that groups together the wide range of concerns in the field of cinema and the environment, and what could be termed "posthuman cinema." It comprises key readings that highlight the centrality of nature and nonhuman animals to the cinematic medium, and to the language and institution of film. The book offers a fresh and timely intervention into contemporary film theory through a focus on the nonhuman environment as principal register in many filmic texts. Screening Nature offers an extensive resource for teachers, undergraduate students, and more advanced scholars on the intersections between the natural world and the worlds of film. It emphasizes the cross-cultural and geographically diverse relevance of the topic of cinema ecology.